Impact of Sodium Alginate and Dried Apple Pomace Powder as a Carrier Agent on the Properties of Freeze-Dried Vegetable Snacks - Magdalena Karwacka; Martyna Gumkowska; Katarzyna Rybak; Agnieszka Ciurzyńska; Monika Janowicz (Polish Journal of Food and Nutrition Sciences, 2021)
The food industry is committed to supplying nutritious products that are attractive and convenient for consumers. Freeze-dried fruit and vegetable snacks that exemplify such products are difficult to obtain since it is necessary to use a carrier agent (usually a hydrocolloid ingredient) which meets the requirements of a sustainable development conceptual framework. Therefore, research has been undertaken to replace such a carrier agent with food waste fruit pomace. This study compared selected physicochemical properties of freeze-dried vegetable snacks obtained through the addition of sodium alginate and dried apple pomace powder in terms of the viability of replacing hydrocolloid carrier agents in freeze-dried products with fruit pomace. Three vegetable sets containing: yellow bean, carrot and potato were prepared and modified by adding diverse carrier agents. Snacks with the addition of dried apple pomace powder featured higher dry matter content and true and apparent density, but sodium alginate-structured products were harder and more porous. Dried apple pomace powder improved the health-promoting properties of the snacks, such as total phenolic content and antioxidant capacity. The type of additive also affected the internal structure of the products. The results indicate that the application of both dried apple pomace powder and sodium alginate as carrier agents can result in snacks characterised by repeatable quality, but it is unclear whether the total replacement of hydrocolloid is sustainably efficient.